1986
DOI: 10.1007/bf00237404
|View full text |Cite
|
Sign up to set email alerts
|

The projection of different retinal ganglion cell classes to the dorsal lateral geniculate nucleus in the hooded rat

Abstract: The morphology of retinal ganglion cells which project to different parts of the dorsal lateral geniculate nucleus (DLG) in the hooded rat has been investigated. Small amounts of a retrograde tracer (horseradish peroxidase) were injected into the DLG, then labelled retinal ganglion cells were examined in retinal wholemounts. After injections into different parts of the DLG, differences were noted in the size, morphology and retinal distribution of labelled retinal ganglion cells. Specifically, after injections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 34 publications
3
51
0
Order By: Relevance
“…In fact, these regional preferences are consistent with studies done in the rat, suggesting that the rodent dLGN is organized into two separate domains; a rostroventral central core comprised of cells that receive input primarily from fast-conducting, large, type I RGCs, and an outer caudodorsal shell comprised of cells that receive input from slowly conducting, smaller type II and III RGCs (Reese, 1988). Additional anatomical evidence seems to support the presence of a third domain, located in the posterodorsal region (i.e., monocular segment) that serves as a recipient zone for subset of smaller type II and III RGCs (Martin, 1986).…”
Section: Discussionmentioning
confidence: 94%
“…In fact, these regional preferences are consistent with studies done in the rat, suggesting that the rodent dLGN is organized into two separate domains; a rostroventral central core comprised of cells that receive input primarily from fast-conducting, large, type I RGCs, and an outer caudodorsal shell comprised of cells that receive input from slowly conducting, smaller type II and III RGCs (Reese, 1988). Additional anatomical evidence seems to support the presence of a third domain, located in the posterodorsal region (i.e., monocular segment) that serves as a recipient zone for subset of smaller type II and III RGCs (Martin, 1986).…”
Section: Discussionmentioning
confidence: 94%
“…In the mouse retina, we identified every subtype of ganglion cells observed in the rat retina (Sun et al, 2002). The mouse RG A1 cells are morphologically equivalent to their counterpart in the rat retina, identified by Perry (1979) as type I cells, by Dreher (1985) and Martin (1986) as class I cells, and by Peichl (1989) and Tauchi et al (1992) as inner alpha cells. The mouse RG A2 cells are also similar to the rat cells represented by Perry's (1979) type I cells, by Peichl's (1989) and Tauchi and colleagues' (1992) outer alpha cells, and in Huxlin and Goodchild's (1997) inner and outer RG A2 cells.…”
Section: Interspecies Comparison and Functional Implicationsmentioning
confidence: 90%
“…Attempts to date to classify rat geniculate cells have failed to do so conclusively (Fukuda et al 1975(Fukuda et al 1979Hale and Sefton 1978;Martin 1986;Reese 1988;Gabriel et al 1996). This leaves two possibilities, among others: relationships between triadic input and certain morphological variables of relay cell exist, but these do not routinely correlate to different types of driver input as they do in the cat's lateral geniculate nucleus, or such a correlation does indeed exist, and the proper classification of retinogeniculate remains to be done for the rat.…”
Section: General Conclusionmentioning
confidence: 99%
“…That is, limited data suggest that the rat lateral geniculate nucleus, like that in the cat, may also consist of subtypes of relay neurons (Lennie and Perry 1981;Martin 1986;Gabriel et al 1996), although this is contentious (Fukuda et al 1975), and whether these triadic arrangements are limited to a specific subgroup of relay neurons is unknown. Our earlier studies in the rat lateral geniculate nucleus clearly demonstrated a TTXsensitive and -insensitive populations of neurons in response to the ACPD, so the data are consistent but not conclusive (Cox and Sherman 2000;Govindaiah and Cox 2004).…”
Section: Introductionmentioning
confidence: 99%